Efficacy and safety of varicocelectomies: A meta-analysis. (4th March 2017) - Yuan, Renbin; Zhuo, Hui; Cao, Dehong; Wei, Qiang
ABSTRACT: This study reviewed the efficacy and safety of the three surgical approaches for varicocele (microsurgical, laparoscopic, and open varicocelectomy). A systematic review of the relevant randomized clinical trials was performed. Trials were identified from specialized trials register of the Cochrane UGDP Group, the Cochrane library, additional electronic searches (mainly MEDLINE, EMBSAE, SCI, CBM), and handsearching. Clinical trials comparing microsurgical, laparoscopic and open varicocelectomies were included. Statistical analysis was managed using Review Manager 5.3. Seven clinical trials of 1, 781 patients were included. The meta-analysis indicated that compared with open varicocelectomy, microsurgery had a higher pregnancy rate ( p =0.002), while there was nonsignificant difference between microsurgical and laparoscopic varicocelectomies or between laparoscopic and open varicocelectomies. Both microsurgical and laparoscopic varicocelectomies had a greater increase in postoperative sperm concentration than open varicocelectomy ( p =0.008 and p =0.001, respectively). Microsurgical varicocelectomy also showed better improvement in postoperative sperm motility ( p =0.02). Compared with the other two, microsurgical varicocelectomy had the longest operative time ( p =0.01 and p =0.0004 respectively). A nonsignificant difference was found in the hospital stay between the three approaches, whereas microsurgical and laparoscopic varicocelectomies had a shorter time to return to work. Moreover, microsurgical varicocelectomy had a lower incidence of postoperative complications and recurrence compared with the others. Analysis of current evidence shows that microsurgical varicocelectomy has a longer operative time, lower incidence of postoperative complications, and recurrence than laparoscopic and open varicocelectomies, and shows a higher pregnancy rate, with a greater increase in postoperative sperm concentration, better improvement in postoperative sperm motility, and shorter time to return to work than open varicocelectomy.